Redistributing medical resources for a bypass strategy for large vessel occlusion: a community-based study. (13th June 2019) - Liu, Ting-Yu; Wang, Chun-Han; Chiang, Wen-Chu; Tang, Sung-Chun; Tsai, Li-Kai; Lee, Chung-Wei; Jeng, Jiann-Shing; Ma, Matthew Huei-Ming; Hsieh, Ming-Ju; Lee, Yu-Ching
Abstract : Background: A bypass strategy for large vessel occlusion (LVO) benefits patients receiving endovascular thrombectomy (EVT), but may delay some patients from receiving IV thrombolysis. However, patient centralization has been shown to improve outcomes. Objective: To understand the current coverage of medical services for patients with stroke, and to identify the best coverage under different medical resource redistribution to help balance medical equality and patient centralization. Methods: This 6-year geographic study of 7679 on-scene patients with suspected stroke with a positive Cincinnati Prehospital Stroke Scale (CPSS) score identified 4037 patients with all three CPSS items who were suspected as having an LVO. Geographic, population, and patient coverage rates for hospitals providing IV thrombolysis and those providing EVT were identified according to hospital service areas, defined as geographic districts with access to a hospital within a ≤15 min off-peak driving time estimated using Google Maps. Moreover, we estimated the effects on resource redistribution when implementing a bypass strategy. Results: Geographic coverage rates for hospitals providing IV thrombolysis and those providing EVT were 64.75% and 56.62%, respectively, and population coverage rates were 97.30% and 92.72%, respectively. The service areas of hospitals providing IV thrombolysis covered 93.77% of patients with suspected stroke, and those of hospitals providing EVT covered 87.89% of patients with suspected LVO. The number of hospitals providing IV thrombolysis and those providing EVT could be reduced to six and two hospitals, respectively, without affecting hospital arrival time when implementing a bypass strategy. Conclusion: Hospitals providing IV thrombolysis and EVT could be reduced without reducing medical equality.